Business analytics approach to artificial intelligence - Gómez-Caicedo, Melva Inés; Gaitán-Angulo, Mercedes; Bacca-Acosta, Jorge; Briñez Torres, Carlos Yesid; Cubillos Díaz, Jenny (Frontiers in Artificial Intelligence, 2022)
Artificial Intelligence has become an essential element for strengthening the business fabric. The advances obtained in recent years as a result of the incorporation of technology for the improvement of productive activities and the positioning of companies in the markets are remarkable. Hence, the purpose of this paper is to analyze the origin, evolution and development of Artificial Intelligence (AI) and its relationship with Business Analytics (BA); from the conceptualization, evolution and identification of the main characteristics and research areas of AI and BA, as well as research conducted and published in journals indexed in Scopus between 2002 and 2022, to establish its impact on business activities. For this purpose, a bibliometric and documentary analysis is applied, allowing to highlight the findings that provide recognition and comparison of the results. This will facilitate the understanding of the current dynamics, its importance for organizations, and its impact in the face of the new challenges generated by the requirements of world trade.